2021
DOI: 10.14203/ann.bogor.2020.v24.n2.106-113
|View full text |Cite
|
Sign up to set email alerts
|

Catechin Contents, Antioxidant and Antibacterial Activities of Different Types of Indonesian Tea (Camellia sinensis)

Abstract: Tea is one of the most popular beverages in the world. Produced from Camellia sinensis leaves, tea has been studied to provide health benefits due to the content of important metabolites. This study aimed to investigate the catechin contents, antioxidant, and antibacterial activities of Indonesian tea varieties, namely green tea, black tea, and white tea. Tea infusion was prepared by extracting 1 g of each sample into 10 mL of distilled water and incubated at 80 °C for 60 min. The catechin and epigallocatechin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although the same tea types (white tea) were subjected, this lower catechin content is thought to be caused by differences in the climate, horticultural techniques, collection time, age of leaf, drying and storage conditions of E white tea. Based on the literature, when the catechin and epigallocatechin gallate contents of white and green tea were compared, it was higher in green tea (12,(24)(25)(26). Furthermore, these results that showed higher catechin proportions found in white tea could explain its high biological activities (anti-oxidant, anti-inflammatory, anti-cancer, anti-diabetic, anti-microbial, and reduced cardiovascular diseases) in comparison to green and black teas (11,(27)(28).…”
Section: Discussionmentioning
confidence: 96%
“…Although the same tea types (white tea) were subjected, this lower catechin content is thought to be caused by differences in the climate, horticultural techniques, collection time, age of leaf, drying and storage conditions of E white tea. Based on the literature, when the catechin and epigallocatechin gallate contents of white and green tea were compared, it was higher in green tea (12,(24)(25)(26). Furthermore, these results that showed higher catechin proportions found in white tea could explain its high biological activities (anti-oxidant, anti-inflammatory, anti-cancer, anti-diabetic, anti-microbial, and reduced cardiovascular diseases) in comparison to green and black teas (11,(27)(28).…”
Section: Discussionmentioning
confidence: 96%
“…The LC-MS/MS analysis of a methanol extract of Corn cobs (Zea mays L.) indicated the presence of bioactive flavonoids (catechin; kaempferol 3-arabinofuranoside 7-rhamnoside; 6,8-Di-C-beta-Darabino pyranosyl apigenin; 5,7-Dihydroxy-8,4'-methoxyisoflavone) (table 2). Catechins have been widely isolated from several plants [28][29][30][31], and it has been reported that catechin has antioxidant [32] and anti-skin aging activities [33]. The kaempferol group and its glycoside derivatives have several activities, such as antioxidants [34,35] and anti-aging [36].…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian sebelumnya menjelaskan bahwa senyawa katekin yang diperoleh dari isolat gambir memiliki pengaruh terhadap pertumbuhan jamur C. albicans (Syarli, 2016). Penelitian lainnya juga menyebutkan ekstrak katekin dari beberapa jenis dapat menghambat bakteri gram positif (lemah) tetapi tidak dapat menghambat gram negatif (Nuryana et al, 2021). Berbeda halnya dengan aktivitas antioksidan, katekin memiliki aktivitas antioksidan yang baik dengan nilai IC50 berkisar 7-40 µg/mL, kategori sangat kuat.…”
Section: Senyawa Metabolit Sekunderunclassified